Generalization of Wye and Delta auto-connections: Analysis of voltages and currents - Da S. Oliveira, Priscila [UNESP]; Fernandes, Rodolfo C. [UNESP]; De Seixas, Falcondes J. M. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Multipulse rectifier topologies based on autoconnections, or differential connections, are more and more applied as interface stages between the mains and power converters. These topologies mitigate many low-order current harmonics in the utility, reducing the THD (total harmonic distortion) and increasing the power factor. This paper presents a mathematical model based on phasor diagrams, that results in a single expression able to unify all differential topologies connections (Delta and Wye), for both step-up or step-down autotransformers, for 12 and 18-pulse AC-DC converters. The proposed family of converters can be designed for any relationship between the input voltage and the load voltage. An immediate application would be the retrofit, i.e. to replace a conventional rectifier with poor quality of the processed energy by the 12 or 18 pulses rectifier with Wye or Delta-differential connection. The design procedure, simple and fast, is developed and tested for a prototype rating 6 kW and 250 V on the DC load © 2010 IEEE.
Keywords: 18-pulse; Ac-dc converters; As interfaces; Current harmonics; DC load; Design procedure; Differential connection; Differential topology; Input voltages; Load voltages; Multi-pulse rectifiers; Phasor diagrams; Power factors; Total harmonic distortions; DC power transmission; Electric power factor correction; Mathematical models; Power converters; Retrofitting; Topology; Electric rectifiers